Potential of a novel brine-struvite-based growth medium for sustainable biomass and phycocyanin production by Arthrospira platensis - Ende, Stephan S. W.; Beyer, Albert S.; Ebaid, Reham; Elshobary, Mostafa; Almeida, Mafalda C.; Couto, Cynthia; Chew, Kit W.; Schwenkler, Tamara; Henjes, Joachim (Frontiers in Bioengineering and Biotechnology, 2024)
Nutrient recovery is crucial for sustainability as it helps to recycle valuable resources, reduce environmental pollution, and promote the efficient use of natural materials in various agricultural and industrial processes. The present study investigated the impact of using brine and struvite as sustainable nutrient sources on the growth and c-phycocyanin (C-PC) production by the cyanobacterium Arthrospira platensis. Three modified growth media were compared to the standard SAG-spirul medium under yellow-white light [YLT], and blue-white light [BLT]. In the modified medium BSI, a struvite solution was utilized to replace dipotassium phosphate, while diluted brine was used to replace NaCl and de-ionized H2O. For BSII, struvite and brine were used as in BSI, with elimination of the micronutrient from the solution. In BSIII, no other nutrient sources than bicarbonate-buffer were used in addition to struvite and brine. For each medium, A. platensis was cultivated and incubated under YLT or BLT till the stationary phase. The results showed that the combinations of brine and struvite did not have any significant negative impact on the growth rates in BSIII. However, adding struvite as a phosphorus source boosted C-PC production just as effectively as YLT, with boosting biomass yield, unlike when only BLT was used. In conclusion, the brine/struvite-based media resulted in high biomass productivity with higher C-PC yields, making it an ideal growth medium for commercial sustainable C-PC production.